Use of different carbon sources in lipase production by Rhizopus oryzae - Bulut, Sule; Tanyldilzi, Muhammet Saban; Ozer, Dursun; Elibol, Murat (Springer India, 2006)
Maximum lipolytic activity (78 mu mol/l-min) was recorded at 1 g/l glucose concentration in the medium in which glucose was the sole carbon source. The inclusion of vegetable oil as an inducer in the fermentation medium resulted in 5 fold higher lipase production compared to the control where no oil was added. Use of olive, soybean, corn, hazelnut and sunflower oils as the sole carbon source increased the lipase production. Maximum lipolytic activity was observed with olive oil when used at 850 mu mol/l-min as sole carbon source.
Keywords: lipase; Rhizopus oryzae; lipolytic activity; inducer; oils